Pengembangan Sistem Informasi E-Permit Menggunakan Metode Rapid Application Development Pada Polsek Semendawai Suku III - Fadhil Ahmad; Vingky Nandra Sari; Tata Sutabri (Syntax Corporation Indonesia, 2024)
The service system for making a crowd permit at the Semendawai Sector III Police is inefficient because people have to come and queue to make the letter. This can slow down the administrative flow, resulting in less public satisfaction with the services of the Semendawai Sector III Police. Therefore, this study aims to develop an e-permit information system to overcome this problem by using the Rapid Application Development (RAD) method. This system can help people apply for a crowd permit online without having to come to the office and send automatic notifications to applicants when the crowd permit is ready to be picked up. The results of the system development using the Rapid Application Development (RAD) method show that this system runs according to needs and accelerates the process of issuing crowd permits so as to provide more optimal and responsive services to the public.